Increasing the Capacity of Teachers and Educational Personnel of Muhammadiyah Susukan Vocational School, Semarang Regency Through Electrical K3 Trainin - Muntasiroh, Laily; Kiswanto, Aris; Hendriansyah, Hendriansyah; Ahdi, Muhammad (Society : Jurnal Pengabdian Masyarakat, 2025)
SMK Muhammadiyah Susukan is a vocational high school offering specialized training programs in three key technical disciplines: electronics engineering, automotive mechanics for light vehicles, and computer networking technologies. The results of observations and interviews with the school, it was found that the understanding and application of electrical K3 at SMK Muhammadiyah Susukan is still far from optimal. The importance of K3 in the field of electricity cannot be underestimated. Based on data from the National Disaster Management Agency (BNPB) and the Ministry of Manpower, incidents related to electricity, including fires and electric shocks, are still one of the main causes of accidents in the workplace and educational institutions. These incidents result in not only financial damages but also create significant safety and health risks for students, educators, and school personnel. Utilizing a pre-experimental one-group pretest-posttest research design, the training involved an initial pretest, theoretical instruction, and a concluding post-test. By applying the Gain test formula to analyze pre- and post-test results, researchers discovered an average N-Gain of 0.68. According to N-Gain assessment criteria, this value signifies a notable improvement in participants' comprehension following the training. The findings demonstrate that the training activity effectively enhanced the knowledge and skills of educational staff and personnel to a moderate degree.